Our Experience with Surgical Treatment of Scaphoid Fractures with Headless Compression Screw - Kostov, Hristijan; Gavrilovski, Andreja; Merdzanoski, Igor; Spasov, Marko; Gjorikj-Petrushevska, Magdalena; Mihajlova-Ilie, Radmila Mila; Kostova, Elena (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Fractures of the scaphoid bone are quite common, and they come with their own set of challenges due to the specific shape of the fractures and the delicate blood supply to the scaphoid bone. Failing to diagnose and treat acute scaphoid fractures promptly can result in failure of the bone to heal and subsequent development of wrist arthritis. Advances in diagnosis, surgery, and implant materials have led to a growing inclination towards early surgical fixation, even for non-displaced scaphoid fractures that could potentially be treated without surgery. AIM: The study's goal was to assess the effectiveness of headless compression screws for treating acute scaphoid fractures and, in two cases, nonunion following previous conservative therapy. METHODS: Between January 2022 and March 2024 ten patients with scaphoid fractures were surgically treated at the University Clinic of Traumatology Skopje, within twelve months follow-up. All of them were male with mean age of 27,3 years. All were diagnosed with X-rays and CT scans. Six of the fractures were on the right hand and four on the left. RESULTS: All the patients were surgically treated with open reduction and internal fixation with headless compression screw. Volar approach was used in 9 cases and dorsal approach in only one of them. Six of the patients were surgically treated within 4-14 days after injury and four of them were surgically treated due to non union after previous conservative treatment, two of them after three and two of them after seven months of injury. All fractures united after a mean time of 9,5 weeks, without secondary displacement. Throughout the follow-up period, there were no incidences of developing osteoarthritis of the wrist. CONCLUSIONS: It is crucial to understand that achieving a positive result is not guaranteed for every patient and relies on selecting the right patients and fractures. However, our study shows favorable results in sooner surgical treatment with the headless compression screw, rather than delayed treatment of scaphoid fractures. Surgical treatment with headless compression screw showed both functional and radiographic results. While it is beneficial for the screw to be positioned in the subchondral area, it is important to be cautious to avoid cortical penetration, as this will require the screw to be removed later.